2008
DOI: 10.1073/pnas.0707881105
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analyses reveal that plant mutagenesis may induce more transcriptomic changes than transgene insertion

Abstract: Controversy regarding genetically modified (GM) plants and their potential impact on human health contrasts with the tacit acceptance of other plants that were also modified, but not considered as GM products (e.g., varieties raised through conventional breeding such as mutagenesis). What is beyond the phenotype of these improved plants? Should mutagenized plants be treated differently from transgenics? We have evaluated the extent of transcriptome modification occurring during rice improvement through transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 41 publications
7
90
0
1
Order By: Relevance
“…The environmental factors lead to changes in physiology and in genome flexibility that can be transferred to next, untreated generations. Batista et al (2008) summarized genes whose expression was altered by microarray analysis into six groups: 1) genes involved in signalling pathways and stress, 2) genes involved in regulatory pathways as second messengers, 3) gene involved in reactive oxygen species (ROS) network; 4) genes implicated in protein modification, 5) genes encoding transcription factors and 6) genes encoding for retrotransposons. They pointed out that similar phenotype does not necessarily mean similar expression profile.…”
Section: Discussionmentioning
confidence: 99%
“…The environmental factors lead to changes in physiology and in genome flexibility that can be transferred to next, untreated generations. Batista et al (2008) summarized genes whose expression was altered by microarray analysis into six groups: 1) genes involved in signalling pathways and stress, 2) genes involved in regulatory pathways as second messengers, 3) gene involved in reactive oxygen species (ROS) network; 4) genes implicated in protein modification, 5) genes encoding transcription factors and 6) genes encoding for retrotransposons. They pointed out that similar phenotype does not necessarily mean similar expression profile.…”
Section: Discussionmentioning
confidence: 99%
“…They reveal that the acquisition of the traits is accompanied by modifications in transcript levels of untargeted stress-related genes, both in transgenic and mutant lines. Moreover, the number of differentially expressed genes appeared to be larger in mutant lines compared to transgenic lines (Batista et al, 2008).…”
Section: "Omics"mentioning
confidence: 99%
“…A difficult issue is to interpret these effects in relation to safety of consumers, nutritional quality or impact on environment. In one study (Batista et al 2008), the observed changes in mRNAs could be contributed to induction of stress to the plant. The consequences of this finding and those published by others remain unclear.…”
Section: Omics Technologies In Risk Assessment For Gmo'smentioning
confidence: 99%
“…Four studies (Batista et al, 2008;Luo et al, 2009;Montero et al, 2011;Xue et al, 2012) compared transgenic rice to wild type rice.…”
Section: Effect Of Transgene On Transcriptomics Difference Between Gmmentioning
confidence: 99%